VD_FINDINFO HC / 2014 / 199 vom 21. Februar 2014 - VD Tribunal cantonal (2014)
ASSISTANCE JUDICIAIRE, INDEMNITÉEN GÉNÉRAL | 122 al. 1 let. a CPC (CH), 2 al. 1 RAJ, 69 al. 3 TFJC (2010), 70 al. 3 TFJC (2010)